2021
DOI: 10.3390/biomedicines9040430
|View full text |Cite
|
Sign up to set email alerts
|

177Lu-PSMA Therapy in Metastatic Castration-Resistant Prostate Cancer

Abstract: The aim of this narrative review is to evaluate the current status of 177Lu-PSMA (prostate specific membrane antigen) therapy for metastatic castration-resistant prostate cancer (mCRPC) in the light of the current literature. We also addressed patient preparation, therapy administration and side effect profiles. 177Lu-PSMA therapy efficacy was assessed by using prospective trials, meta-analyses and major retrospective trials. Predictors of efficacy were also mentioned. Although there are some different approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 68 publications
(119 reference statements)
1
19
0
1
Order By: Relevance
“…with PSA-RRs ranging from 20% to 88% and PFS ranging from 3 to 15.2 months. 4,29,30 In the current study, PSMA-RLT was associated with similar response and survival outcomes. In the absence of a significant role played by the genomic characteristics, these outcomes need to be seen in the context of our highly selected cohort of mCRPC patients who were heavily pretreated with multiple lines of treatment, and had extensive, progressive tumor burden.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…with PSA-RRs ranging from 20% to 88% and PFS ranging from 3 to 15.2 months. 4,29,30 In the current study, PSMA-RLT was associated with similar response and survival outcomes. In the absence of a significant role played by the genomic characteristics, these outcomes need to be seen in the context of our highly selected cohort of mCRPC patients who were heavily pretreated with multiple lines of treatment, and had extensive, progressive tumor burden.…”
Section: Discussionsupporting
confidence: 61%
“…Despite encouraging results from the recent TheraP and VISION trials, real‐world PSMA‐RLT‐related outcomes have been mixed with PSA‐RRs ranging from 20% to 88% and PFS ranging from 3 to 15.2 months 4,29,30 . In the current study, PSMA‐RLT was associated with similar response and survival outcomes.…”
Section: Discussionmentioning
confidence: 59%
“…With a reported radiation exposure dose of 0.39-0.99 Gy/GBq for each kidney [ 3 ] and theoretically 0.78-1.87 Gy/MBq in the case where a single kidney is present, optimal functioning of the kidneys is a major factor to be ruled out prior to RLT. 99m Tc-Diethylene triamine penta-acetic acid (DTPA) renal scan, as performed in our patient, has an established high sensitivity and effectiveness in the evaluation of the dynamic functional status of the kidney(s) and GFR estimation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…As PSMA is physiologically and specifically expressed in the apical epithelium of proximal renal tubules, possible nephrotoxicity is always suspected as each kidney is exposed to an average absorbed radiation dose of 0.39-0.99 Gy/GBq individually [ 3 ] as reported on post-therapy dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…Sandström et al concluded that individualized absorbed doses were essential for optimization [ 37 ], and prospective dosimetry based on a 23 Gy threshold for Lu-177 [ 38 ] and 37 Gy for Y-90 DOTATOC [ 39 ] is feasible to reduce renal toxicity. 177 Lu-PSMA (a beta emitter on prostate-specific membrane antigen) therapy efficacy was assessed by using prospective trials, meta-analyses, and major retrospective trials [ 40 ] to be generally safe, with a low toxicity profile, which is a promising treatment in patients with metastatic castration-resistant prostate cancer with good clinical efficacy [ 40 ]. Similarly, Radium Ra-223 dichloride (radium-223, Xofigo ® ) is a targeted alpha therapy also approved for the treatment of castration-resistant prostate cancer with symptomatic bone metastases and no known visceral metastatic disease [ 41 ].…”
Section: Nuclear Medicine Molecular Radionuclide Treatmentmentioning
confidence: 99%